Alginate graft polyacrylonitrile beads for the removal of lead from aqueous solutions - Salisu, Ahmed (2016)
Grafting of polyacrylonitrile with sodium alginate was carried out in aqueous medium using benzoyl peroxide (BPO) as initiator. The grafting conditions such as monomer, initiator concentration, reaction time and temperature were optimized. The graft copolymers were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, solid-state 13C-nuclear magnetic resonance and scanning electron microscopy. Optimum percentage grafting was obtained when the concentrations of BPO, acrylonitrile and sodium alginate were 6.19 × 10−3, 7.53 × 10−1 mol L−1 and 1 % w/v, respectively. The optimum reaction temperature and reaction time were 80 °C and 4 h, respectively. The copolymer sample with optimum percentage grafting was evaluated for the removal of lead ions from aqueous solutions in batch mode systems. Langmuir and Freundlich isotherm models were applied to describe the adsorption process. The adsorption data fitted into Langmuir model better than Freundlich model with maximum adsorption capacity of 454 mg g−1 (2.20 mmol g−1) while the kinetic data correlated well to pseudo-second-order kinetic model. The adsorbent could be regenerated using HNO3 as elution solvent, and reused repeatedly without significant loss of its metal adsorption capacity.